Genetic polymorphisms analysis of pharmacogenomic VIP variants in Bai ethnic group from China. Issue 9 (30th July 2019) - Chen, Wanlu; Ding, Heng; Cheng, Yujing; Li, Qi; Dai, Run; Yang, Xin; Zhang, Chan
Abstract: Background: The pharmacogenomics study has been widely used for the study of very important pharmacogenetic (VIP) variants among different ethnic groups. However, there is little known about the pharmacogenomics information regarding Bai family. Our study aimed to screen the polymorphism of the VIP gene in Bai nationality. Methods: We genotyped 81 VIP variants (selected from the PharmGKB database) in the Bai population and then compared them to the other 11 major HapMap populations by chi‐square test, structure and F‐statistics (Fst) analysis. Results: Our results indicated that rs20417 ( PTGS2 ), rs4148323 ( UGT1A ), and rs1131596 ( SLC19A1 ) were most different in Bai compared with most of the 11 populations from the HapMap data set. Furthermore, population structure and F‐statistics (Fst) analysis also demonstrated that the Bai population has the closest genetic relationship with Han Chinese in Beijing, China (CHB), followed by Japanese in Tokyo, Japan (JPT), and the farthest population from the Yoruba in Ibadan, Nigeria (YRI). Conclusions: Our study not only presented the genotype frequency difference between the selected population of the Bai population and the other 11 populations, but also showed that the Bai population is most similar to the CHB populations, followed by JPT. These findings would contribute to the development of individualized medicine for the Bai population. Abstract : Our study not only presented the genotype frequency difference between the selected population of the Bai population and the other 11 populations, but also showed that the Bai population is most similar to the CHB populations, followed by JPT. These findings would contribute to the development of individualized medicine for the Bai population.